2013
DOI: 10.1111/acer.12141
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effects of Alcohol on Sleep Architecture in Late Adolescence

Abstract: Background Alcohol consumption is prevalent in late adolescence, however little is known about its effect on sleep in this group. In mature adults, alcohol decreases sleep onset latency (SOL) and sleep efficiency (SE) and increases wake after sleep onset (WASO). It also increases slow wave sleep (SWS) and decreases REM sleep in the first half of the night, with the inverse occurring in the second half. Alcohol’s effect on sleep during late adolescence is of interest given that this age group shows both dramati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 47 publications
3
30
0
2
Order By: Relevance
“…Women also reported higher ratings of sleepiness after consuming alcohol than did men. No sex differences in the effects of alcohol on sleep were seen in the group of older adolescents studied by Chan et al (Chan et al 2013). In a study of 42 recovering alcoholics (15 women) and 42 controls (23 women), we found that women had a better sleep efficiency and more delta activity during NREM sleep than men, regardless of diagnosis (Colrain, Turlington, and Baker 2009a).…”
Section: 0 Sleep In Alcoholismmentioning
confidence: 80%
See 2 more Smart Citations
“…Women also reported higher ratings of sleepiness after consuming alcohol than did men. No sex differences in the effects of alcohol on sleep were seen in the group of older adolescents studied by Chan et al (Chan et al 2013). In a study of 42 recovering alcoholics (15 women) and 42 controls (23 women), we found that women had a better sleep efficiency and more delta activity during NREM sleep than men, regardless of diagnosis (Colrain, Turlington, and Baker 2009a).…”
Section: 0 Sleep In Alcoholismmentioning
confidence: 80%
“…Alcohol initially acts as a sedative. Commonly reported phenomena include shortened sleep onset latency (MacLean and Cairns 1982; Roehrs et al 1999; Williams, MacLean, and Cairns 1983; Stone 1980; Scrima et al 1982) and increased SWS in the first half of the night (Williams, MacLean, and Cairns 1983; Van Reen, Jenni, and Carskadon 2006; Sagawa et al 2011; Rundell et al 1972; Chan et al 2013; MacLean and Cairns 1982; Prinz et al. 1980; Feige et al 2006; Arnedt, Rohsenow, et al 2011).…”
Section: 0 Acute Effects Of Alcohol On Sleepmentioning
confidence: 99%
See 1 more Smart Citation
“…SWS-rebound during the second night could possibly be able to mask the effects on pain of SWS-deprivation (Onen et al, 2001). However, real SWS-rebound, including any cognitive effect thereof, was probably minimal, as N3 was about 88 min in the four hours sleep group and 101 min in the nine hours sleep group, and about 80% of N3 is expected to occur within the first half of sleep in young adults (Chan et al, 2013).…”
Section: Tablementioning
confidence: 98%
“…Алкоголь, принятый непосредственно перед сном, действует как транквилизатор: характерна меньшая продолжительность периода засыпания и уси-ление медленно-волновой активности в первой полови-не ночного сна [30]. Фаза быстрого REM сна подавлена и укорочена [6]. Во второй половине ночного сна сон прерывается, представленность REM-сна увеличивается.…”
Section: влияние однократного приема алкоголя на сонunclassified